Analysis of human protein and energy metabolism: application of a new method in sports - Huelsemann, F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
For many years the analysis of nitrogen stable isotope ratio analysis at natural abundances of animal tissue and urinary components has been used in ecology. Isotope ratio mass spectrometry (IRMS) was used for the interpretation of nutritional status and metabolic conditions of individuals and populations as well as for the exploration of food webs. For humans it has been shown that anabolic or catabolic conditions can be identified by segmental analysis of hair. Due to isotopic fractionation during nitrogen metabolism within the body dietary and body nitrogen exhibit significantly different natural isotope ratios. Therefore variations in natural stable nitrogen isotope ratios of tissue or urea allow for the estimation of the proportion of metabolized body nitrogen in comparison to dietary nitrogen. IRMS of natural variations in nitrogen isotopes expand the scope of analytical methods for studies of energy and protein metabolism in addition to conventional tracer experiments. In contrast to tracer experiments studies at natural isotope ratios do no require administration of labeled substances. Whereas nitrogen isotope ratio analysis of urea provides information about actual metabolic conditions the analysis of human hair enables a retrospective examination of an individual`s energy and protein metabolism. By IRMS of segmented hair we were able to identify catabolic and anabolic conditions of an athlete`s metabolism that resulted from varying nutritional statuses and levels of physical activity. Nitrogen isotope ratios of hair segments were significantly associated with energy balance and protein intake. Identical patterns of correlation between natural stable nitrogen isotope ratios and energy balance and protein intake were detected by IRMS of urinary urea for athletes prior, during and after a 24-hour bicycle race. In contrast to the period before the race, during the race an increased excretion of body nitrogen could be detected by IRMS for the athletes with the most negative energy balance and the lowest protein intake. After the race an inverse situation was reached as athletes excreted high amounts of isotopically light nitrogen due to high amounts of protein intake. Variations in natural nitrogen isotope ratios of urea yield additional information about the human energy and protein metabolism when compared to excreted urea concentrations. The analysis of natural stable nitrogen isotope ratios of human tissue and urinary components is capable to provide additional insights into human energy and protein metabolism besides existing analytical techniques.